Infusion of Host-Derived Unlicensed NK Cells Improves Donor Engraftment in Non-Myeloablative Allogeneic Hematopoietic Cell Transplantation - Maite Alvarez; Maite Alvarez; Maite Alvarez; Maite Alvarez; Antonio Pierini; Federico Simonetta; Jeanette Baker; Kristina Maas-Bauer; Toshihito Hirai; Robert S. Negrin (Frontiers in Immunology, 2021)
Allogeneic hematopoietic cell transplantation (allo-HCT) is an efficacious and frequently the only treatment option for some hematological malignances. However, it often faces severe morbidities and/or mortalities due to graft versus host disease, and the severity of the conditioning regiment needed, that result in toxicity-related issues poorly tolerable for some patients. These shortcomings have led to the development of less aggressive alternatives like non-myeloablative (NMAC) or reduced-intensity conditioning regiments (RIC). However, these approaches tend to have an increase of cancer relapse and limited persistence of donor-specific chimerism. Thus, strategies that lead towards an accelerated and more durable donor engraftment are still needed. Here, we took advantage of the ability of host-derived unlicensed NK (UnLicNK) cells to favor donor cell engraftment during myeloablative allo-HCT, and evaluated if the adoptive transfer of this cell type can improve donor chimerism in NAMC settings. Indeed, the infusion of these cells significantly increased mixed chimerism in a sublethal allo-HCT mouse model, resulting in a more sustainable donor cell engraftment when compared to the administration of licensed NK cells or HCT controls. We observed an overall increase in the total number and proportion of donor B, NK and myeloid cells after UnLicNK cell infusion. Additionally, the extension and durability of donor chimerism was similar to the one obtained after the tolerogenic Tregs infusion. These results serve as the needed bases for the implementation of the adoptive transfer of UnLicNK cells to upgrade NMAC protocols and enhance allogeneic engraftment during HCT.